Eccentric flywheel post-activation potentiation influences swimming start performance kinetics - Cuenca-Fernández, F.; López-Contreras, G.; Mourão, L.; de Jesus, Ka.; de Jesus, Ke.; Zacca, R.; Vilas-Boas, J. P.; Fernandes, R. J.; Arellano, R. (Journal of Sports Sciences, 2019)
This study aimed to assess the effects of post-activation potentiation in the strength related variables of a kick start. Thirteen competitive swimmers performed three kick starts after a standardized warm up (denoted USUAL) and another after inducing post-activation through five isotonic repetitions on an eccentric flywheel (denoted PAP). A T-test was used to quantify differences between USUAL and PAP warm up. The best trial of each subject achieved by natural conditions (denoted PEAK) was compared with data obtained after PAP. An instrumented starting block with independent triaxial force plates, collected the strength variables related with the impulse at take off. Improvements in the vertical components of force were observed after PAP compared with USUAL, meanwhile no differences were detected on the horizontal components of it. The velocity at take off was higher after PAP compared with USUAL (4.32 ± 0.88 vs 3.93 ± 0.60 m/s; p = 0.02). No differences in force or velocity were detected comparing PAP with PEAK (4.13 ± 0.62 m/s, p = 0.11). The PAP warm-up increased vertical force and it was transferred to a higher resultant velocity at take-off. This improvement would equal the best result possible obtained in natural conditions after some trials.